Contribution of apoptosis-associated signaling pathways to epileptogenesis: lessons from Bcl-2 family knockouts - Henshall, David; Engel, Tobias (Frontiers in Cellular Neuroscience, 2013)
Neuronal cell death is a pathophysiological consequence of many brain insults that trigger epilepsy and has been implicated as a causal factor in epileptogenesis. Seizure-induced neuronal death features excitotoxic necrosis and apoptosis-associated signalling pathways, including activation of multiple members of the Bcl-2 gene family. The availability of mice in which individual Bcl-2 family members have been deleted has provided the means to determine whether they have causal roles in neuronal death and epileptogenesis in vivo. Studies show that multiple members of the Bcl-2 family are activated following status epilepticus and the seizure and damage phenotypes of eight different knockouts of the Bcl-2 family have now been characterized. Loss of certain pro-apoptotic members, including Puma, protected against seizure-induced neuronal death whereas loss of anti-apoptotic Mcl-1 and Bcl-w enhanced hippocampal damage. Notably, loss of two putatively pro-apoptotic members, Bak and Bmf, resulted in more seizure-damage while deletion of Bid had no effect, indicating the role of certain Bcl-2 family proteins in epileptic brain injury is distinct from their contributions following other stressors or in non-CNS tissue. Notably, Puma-deficient mice develop fewer spontaneous seizures after status epilepticus suggesting neuroprotection may preserve functional inhibition, either directly by preserving neuronal networks or indirectly, for example by limiting reactive gliosis and pro-inflammatory responses to neuronal death. Together, these studies support apoptosis-associated molecular mechanisms controlling neuronal death as a component of epileptogenesis which might be targetable to protect against seizure-damage, cognitive deficits and mitigate the severity of syndrome following epilepsy-precipitating injuries to the brain.